2017
DOI: 10.1186/s13021-017-0072-2
|View full text |Cite
|
Sign up to set email alerts
|

Greenhouse gas emissions from tropical forest degradation: an underestimated source

Abstract: BackgroundThe degradation of forests in developing countries, particularly those within tropical and subtropical latitudes, is perceived to be an important contributor to global greenhouse gas emissions. However, the impacts of forest degradation are understudied and poorly understood, largely because international emission reduction programs have focused on deforestation, which is easier to detect and thus more readily monitored. To better understand and seize opportunities for addressing climate change it wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
228
0
8

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 335 publications
(239 citation statements)
references
References 20 publications
3
228
0
8
Order By: Relevance
“…Moreover, under deforestation the moisture storage capacity decreases, affecting the local energy budget, i.e., sensible heating increases whereas latent heating decreases [7]. Deforestation/land use change also contributes to increased greenhouse gas emissions into the atmosphere [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, under deforestation the moisture storage capacity decreases, affecting the local energy budget, i.e., sensible heating increases whereas latent heating decreases [7]. Deforestation/land use change also contributes to increased greenhouse gas emissions into the atmosphere [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, its function as important carbon sinks is well known, capturing about 15% of anthropogenic carbon emissions on a global scale [15,16]. Yet, deforestation and forest degradation processes are responsible for significant losses and reductions in carbon stocks [17][18][19][20][21]. On a global scale, using data from the FAO Forest Resource Assessment (FRA), Federici et al [22] found an average rate of carbon emissions of 4.0 Gt CO 2 year −1 during the 2001-2010 decade, decreasing to an estimated rate of 2.9 Gt CO 2 year −1 between 2011 and 2015 coming fundamentally from forest conversion.…”
Section: Introductionmentioning
confidence: 99%
“…In the 2000s, carbon emissions coming from deforestation in the tropics were in the range of 0.6 to 1.2 Gt C year −1 [23][24][25]. Moreover, in a recent study focusing on the tropical and subtropical regions, Pearson et al [21] estimated that, between 2005 and 2010, about 6.22 and 2.1 Gt CO 2 were emitted every year from deforestation and forest degradation respectively. In this regard, it has been mentioned in the literature that these emissions are equivalent to 10-20% of total global carbon emissions [25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, in these areas the moisture storage capacity decreases affecting both sensible and latent heat fluxes, i.e., the sensible heating increases while the latent heting decreases [7]. Deforestation/land use change aslo contributes as a source of greenhouse gas emissions into the atmosphere [8]. Wood is a sink or storage place for carbon, but with burned, carbon dioxide (CO2) is release into the atmposphere.…”
Section: Introductionmentioning
confidence: 99%